From populism to climate scepticism: the role of institutional trust and attitudes towards science. Issue 7 (10th November 2022) - Huber, Robert A.; Greussing, Esther; Eberl, Jakob-Moritz
ABSTRACT: Why do populist citizens oppose climate change? Thus far, data constraints limited the ability to test different theoretical mechanisms against each other. We argue that populist attitudes affect climate attitudes through two distinct channels, namely institutional trust and attitudes towards science. The former argument focuses on political institutions as the central actors in implementing climate policy. Individuals who distrust these institutions are more sceptical about climate change. The latter argument claims that populists deny climate change because they distrust the underlying climate science. According to this view, populists would view climate scientists as part of the self-serving elite that betrays the people. Utilising data from the Austrian National Election Study and structural equation modelling, we find strong support for the relationship of populism and climate attitudes via attitudes towards science and institutional trust. Populists systematically hold more negative attitudes towards science and political institutions, and consequently deny climate change.